Family Farmers' Perceptions of the Impact of Public Policies on the Food System: Findings From Brazil's Semi-Arid Region - Brandão, Emily Aparecida Ferreira; Santos, Thiago da Rocha; Rist, Stephan (Frontiers in Sustainable Food Systems, 2020)
The global narrative on food sustainability revolves around the need to improve food security, right to food, environmental performance, social-ecological resilience, reducing poverty, and inequality. Such principles were guiding a food policy shift for addressing the needs of family farmers, taking place in Brazil. However, how these policies were seen from the point of view of family farmers has not yet been investigated sufficiently. Consequently, this paper presents the results of an assessment of how food policies have impacted the food system in terms of production practices, market structure, land access, and food security, through the perception of family farmers. Our study concerns the semi-arid part of the state of Bahia (Brazil), in which rainfed food systems prevail. The perception of family farmers on the food policies related to credit, public procurement, technology, knowledge, and land access showed three main results: (1) concerning production practices, there was an increase in crop diversification (formerly collected wild plants are currently cultivated) and the dissemination of agro-ecological techniques (organic matter as a fertilizer and seed bank). However, credit is limited, not being translated into significant investments in the production process; (2) with regard to market structure, the public food procurement programs created a specific market for farmers assuring to provide reliable and stable income and trade through economies of scale. The negative factor regarding public food procurement programs is the dependence of farmers from institutional markets organized by the government; (3) food security was increased, due to the stable income, but the lack of policies directed at on-farm autonomy makes production for self-consumption difficult to be achieved. Also, the legal basis for land access does not meet the expectations and needs of farmers, placing them in a position of vulnerability to land grabbing. We conclude that the new food public policies had positive impacts, through a double strategy, consisting in first, the improvement of individual food system activities, and second, interconnecting single food system activities in such a way that they create synergies among them, in view of basic principles of sustainable food systems.